Main approaches to the classification of Scottish dictionaries (written in Scots and Scottish Gaelic) - Lemeshchenko-Lagoda, Viktoriia; Лемещенко-Лагода, Вікторія Володимирівна; Лемещенко-Лагода, Виктория Владимировна (My University, 2021)
Unusual intensity of information and communication activities of the late twentieth century identified the rapid development of various areas of applied linguistics, mostly lexicography. Most authoritative Ukrainian dictionaries define the concept 39 of “lexicography” in two aspects - theoretical and practical. Theoretical lexicography or metalexicography is considered as the purposeful scientific knowledge that gives a holistic systematic view of all issues related to the compilation of dictionaries, and practical or applied lexicography, which has accumulated extensive experience in the orderly and systematic description of languages, in its turn, is associated with direct practice of compiling dictionaries.
Keywords: scottish dictionaries; lexicography; Scottish computer dictionaries